A linguagem verbal das artes visuais: uma análise multidimensional do discurso sobre a fotografia de Sally Mann - Romeiro, Yara Maria de Toledo Dias (2020)
Texts about the visual arts perform important functions in the field, supporting, highlighting, describing, assessing, educating about, and theorizing on the artistic object itself (cf. LAZZERETTI, 2016). Based on such discourse, art theories are formed and concepts through which art is regarded and assessed are developed. The objective of this study is to investigate the discursive universe of Sally Mann’s photography from a lexical-based Multidimensional Analysis (BERBER SARDINHA, 2014, 2017, 2019), which is a statistically-based approach capable of detecting groups of lexical items that co-occur in texts, revealing recurrent themes in the language used in the texts. To conduct this investigation, a corpus composed of 555 texts (approximately 765.000 words), depicting the discourse about American photographer Sally Mann was collected and analyzed. The corpus comprises 12 different registers, including photography books written by the artist, wall texts from her exhibitions and articles from the general and specialized press, among others, taken from Mann's official library and public archives and covering a period of over 30 years. The texts were cleaned up, then lemmatized and tagged for part-of-speech with the TreeTagger software. A script revealed the most prominent lemmas, counted, and normed their occurrences. The normed counts were submitted to a factorial analysis in SAS University Edition. The resulting seven factors were interpreted as lexical dimensions related to the themes underlying Mann’s photographic work, centered on the North American South, the fascination with mortality, and family relations. This study aims to contribute to the use of empirical, corpus-based linguistic studies as a tool to investigate art and its discourse